"Níveis dietéticos de proteína bruta sobre o metabolismo de nitrogênio" - Araújo, Laylles Costa (2017)
Two experiments were carried out at the Experimental Station, Prof. Dr. Antônio Carlos Pessoa belonging to the Wetern Paraná State University UNIOESTE, from August 2015 to June 2016. In the experiment I, the objective was to evaluate the relationship between the excretion of respiratory ammonia (RA) and the crude protein content of the diet. Four Holstein heifers were used, with an average body weight of 252.8 ±9.8 kg at the beginning of the experiment. The experimental design used was the latin square 4x4. The animals were fed diets with a bulky ratio: concentrate of 45:55, comprising the treatments of 9%, 12%, 15% and 18% crude protein in the diet, evaluating the excretion of respiratory ammonia (RA), concentration of Ammonia (AS), serum urea nitrogen (NUS), and urine nitrogen (N) excretions. The concentration of RA was not influenced (P>0.05) by the diets and there was no effect of collection times. The initial concentration (Ci) and the final concentration (Cf) of ammonia were similar to 48.30 ppb and 48.60 ppb, respectively. This indicates that ammonia excretion through respiration was almost null. The concentration of AS and NUS had a linear increase (P<0.05), the excretion of total nitrogen had a linear effect (P<0.05). Experiment 2 was conducted to evaluate the influence of crude protein levels on nutritional parameters. The animals, experimental design, treatments and diets were similar to experiment 1. Reduction in dry matter intake, organic matter and non-fibrous carbohydrates (P<0.05) and increase in crude protein intake (P<0.05) were obtained. The digestibility of dry matter, crude protein, non-fibrous carbohydrates and total digestible nutrients increased with crude protein levels in the diet (P<0.05). Excretions of urea nitrogen in the urine, nitrogen excretions in the urine, nitrogen balance and serum urea nitrogen had a linear increase (P<0.05). The pH was not influenced (P>0.05), however, the concentrations of nitrogen in the ruminal fluid increased linearly (P<0.05). Therefore, there is no excretion of respiratory ammonia with increasing levels of crude protein in the diet, as well as does not interfere with digestibility and ruminal pH, but reduces dry matter intake and organic matter, and increases the excretion of urinary nitrogen.